Does natural honey have beneficial effect on honamlı buck semen during liquid storage? - Şükrü Güngör; Muhammed Enes İnanç; Sezgin Akyüz; Elif Andıl; Ayhan Ata (Eurasian Journal of Veterinary Sciences)
Aim: Honey has been produced by honey bee comprises high level of sugars which could be beneficial effects on spermatozoa. The main goal of this study was to determine the natural honey addition on the spermatological parameters of Honamlı buck spermatozoa during liquid storage at 4 °C up to 96 hours. Materials and Methods: At the breeding season a total of three Honamlı bucks were used in this study. Four extenders were prepared with tris-egg yolk first was as a control (no honey added) and others had concentrate as 1, 3 and 6% honey into the base extender. Sperm parameters were assessed including subjective motility, membrane integrity and abnormality at 0, 24, 48, 72 and 96 th hours. Results: The motility of Honamlı buck spermatozoa was higher control and 1% honey added group compared the 3% and 6% up to 96 hour (p<0.05). On the other hand 3 and 6% honey supplemented groups motility was getting worse until 24th hour (p<0.05). While membrane integrity results have shown that only 1% honey addition group higher than the other honey groups (p<0.05). Conclusion: Our data suggested that 1% honey could be added to Tris based extender for improving the Honamlı buck sperm quality in short term storage.